2007
DOI: 10.1038/sj.onc.1210317
|View full text |Cite
|
Sign up to set email alerts
|

Selective suppression of lymphomas by functional loss of Hsf1 in a p53-deficient mouse model for spontaneous tumors

Abstract: A hallmark in the pathogenesis of cancer is the increased expression of heat shock proteins (Hsps) and other molecular chaperones observed in many tumor types, which is considered to be an adaptive response to enhance tumor cell survival. Heat shock transcription factor 1 (Hsf1) is a major transactivator of Hsp induction and has been proposed to affect tumor initiation and progression, regulating expression of Hsps and other molecular targets. In this report, we provide direct in vivo evidence that Hsf1 plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
139
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 30 publications
9
139
2
1
Order By: Relevance
“…In line with these results, different animal experiments with genetically modified mice showed an essential role of HSF1 in tumor development (26,27,63) (Table II).…”
Section: Hsf1 and Cancersupporting
confidence: 69%
“…In line with these results, different animal experiments with genetically modified mice showed an essential role of HSF1 in tumor development (26,27,63) (Table II).…”
Section: Hsf1 and Cancersupporting
confidence: 69%
“…Although still not well understood, the functions of HSF1 are beyond the classical induction of heat shock responses. Recent reports have shown that HSF1 may have an important role in cancer development (Khaleque et al, 2005(Khaleque et al, , 2008Min et al, 2007). A recent study showed that the elimination of HSF1 protects mice from tumors induced by mutations of the Ras oncogene or a hot spot mutation in the tumor suppressor p53 (Dai et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The roles of HSPs in tumor development may also be related to their functions in the development of tolerance to applied stress (Li and Werb, 1982). However, the precise relationships between HSFs and HSPs during cancer development have not been clearly defined and relatively few papers about the role of HSF1 in cancer or carcinogenesis are available (Cen et al, 2004;Wang et al, 2004;Min et al, 2007).…”
Section: Introductionmentioning
confidence: 99%